2021
DOI: 10.15835/nbha49111998
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen form and root division modifies the nutrimental and biomolecules concentration in blueberry (Vaccinium corymbosum L.)

Abstract: Blueberry (Vaccinium corymbosum L.) continues to gain importance in the international market due to its effects on the prevention of human diseases. This leads to the need to optimize the production and quality of the fruit. The present research evaluated the effect of NO3- and NH4+, using the split roots technique, in the nutritional status, photosynthetic pigments and total sugars in blueberry leaves. A completely random experiment was established with six greenhouse treatments: three under homogeneous root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…In some cultivars there was no change in concentration in several of the macronutrients evaluated against the increasing NH4-N dose. This effect can be explained by the genotypic and phenotypic differences of the cultivars evaluated, as has been pointed out for blueberries by different authors (Bañados et al, 2012;Strik and Vance, 2015;Bryla et al, 2021;Leal-Ayala et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In some cultivars there was no change in concentration in several of the macronutrients evaluated against the increasing NH4-N dose. This effect can be explained by the genotypic and phenotypic differences of the cultivars evaluated, as has been pointed out for blueberries by different authors (Bañados et al, 2012;Strik and Vance, 2015;Bryla et al, 2021;Leal-Ayala et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Bañados et al (2012) andStrick andVance (2015) reported a directly proportional effect on N concentration. Leal-Ayala et al (2021) reported an increase in the concentrations of N, P and Mg. The higher concentration obtained in some macronutrients when applying increasing rates of ammoniacal N can be associated with the nutritional functions of N in the plant and its effect on metabolic, structural, enzymatic and electron transport activities of the other nutrients (Marschner, 2002;Maathuis, 2009).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation